Physics of astroparticles - Sciutto, Sergio Juan (2007)
The measurement of the properties of the highest energy astroparticles that hit the Earth's atmosphere is a challenging problem that the Auger experiment tries to solve. In this talk we present a general description of several aspects of the interactions between those high energy particles and the Earth's atmosphere, focusing in primary reconstruction. Special attention is dedicated to work done in our group regarding analysis performed with the help of air shower simulations.